Disseminated Intraabdominal Echinococcosis: A Case Report - Gangadhar, K; Santhosh, D; Goel, K; Rana, S; Jain, S (Nepalese Journal of Radiology, 2012)
Human hydatid disease results from infection with larval form of Echinococcus granulosus. The disseminated intra-peritoneal hydatid disease is a very rare finding. A case of disseminated intra abdominal hydatid disease is presented along with a review of literature and various therapeutic modalities. NJR I VOL 2 I ISSUE 1 50-53 Jan-June, 2012 DOI: http://dx.doi.org/10.3126/njr.v2i1.6982